2012
DOI: 10.1152/ajpcell.00273.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential determinants for coupling of distinct G proteins with the class B secretin receptor

Abstract: The secretin receptor is a prototypic class B G protein-coupled receptor that is activated by binding of its natural peptide ligand. The signaling effects of this receptor are mediated by coupling with Gs, which activates cAMP production, and Gq, which activates intracellular calcium mobilization. We have explored the molecular basis for the coupling of each of these G proteins to this receptor using systematic site-directed mutagenesis of key residues within each of the intracellular loop regions, and studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…The KxxK 6.35 motif may interact with the C-terminus of Gαs, aided by flexing of TM6 around P 6.42 (class B) or P 6.50 (class A). This interaction is born out by MD simulations, but the analogous residues in the β 2 -AR–Gs complex (PDB code 3SN6) are poorly resolved and so the interpretation should be used with care, despite the observations from mutagenesis experiments that implicate K 6.32 and K 6.35 in G-protein coupling in both class A [36,46–48] and class B [39,4952] GPCRs. For this reason, it is important to note that the alignment is based on mutagenesis results throughout the transmembrane region and not in just one region, such as the G-protein coupling region.…”
Section: Resultsmentioning
confidence: 99%
“…The KxxK 6.35 motif may interact with the C-terminus of Gαs, aided by flexing of TM6 around P 6.42 (class B) or P 6.50 (class A). This interaction is born out by MD simulations, but the analogous residues in the β 2 -AR–Gs complex (PDB code 3SN6) are poorly resolved and so the interpretation should be used with care, despite the observations from mutagenesis experiments that implicate K 6.32 and K 6.35 in G-protein coupling in both class A [36,46–48] and class B [39,4952] GPCRs. For this reason, it is important to note that the alignment is based on mutagenesis results throughout the transmembrane region and not in just one region, such as the G-protein coupling region.…”
Section: Resultsmentioning
confidence: 99%
“…Cell surface expression of secretin receptor mutants that exhibited no saturable binding. COS‐1 cells transiently expressing each of the noted secretin receptor mutant constructs were analyzed by flow cytometry using an amino‐terminal region secretin receptor antibody (18). Data represent percentage expression levels of each mutant relative to wild type receptor, expressed as means ± se of 3 independent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…However, mutation analysis showed that this motif did not affect the calcium responses in human SCTR (Garcia et al 2012). Although Lys242 is conserved in secretin receptors, Arg241 is not conserved across different species, suggesting that this motif is not involved in controlling G-protein functioning in SCTR.…”
Section: Motifs For Signal Transductionmentioning
confidence: 93%
“…It has been reported that the His165 in TM2 is essential for the surface expression of secretin receptor. Mutation of this His residue (H166A or H166R) in human SCTR decreases the ligand-binding affinity, as well as cAMP response and calcium signaling, thus suggesting the poor surface expression of these mutants (Garcia et al 2012). Lys312 and Leu313 residues in the ICL3 are important for cAMP signaling in human SCTR (Garcia et al 2012) and also in other secretin GPCRs (Mathi et al 1997, Marie et al 2003.…”
Section: Motifs For Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation